Labor Unions and Race-conscious Housing in the Postwar Bay Area: Housing Projects of the International Longshoremen's and Warehousemen's Union and the United Automobile Workers. (August 2016) - Botein, Hilary
This article examines two racially integrated labor union-sponsored housing cooperatives developed in the San Francisco Bay Area in the 1950s and 1960s. The projects offer examples of small-scale alternative paths to postwar suburbanization and inner-city decline. St. Francis Square, in the Western Addition neighborhood of San Francisco, was sponsored by the International Longshoremen's and Warehousemen's Union. Sunnyhills, in the newly incorporated town of Milpitas in Santa Clara County, was sponsored by the United Automobile Workers. The projects illustrate how the postwar strategies of growth liberalism and the urban growth machine, which facilitated private investment and racial segregation in the service of economic development, simultaneously expanded and checked municipal and labor union priorities.